Richard II and the rebel earl - Gundy, A. K. (Cambridge studies in medieval life and thought, 2013)
The reign of Richard II and the circumstances of his deposition have long been subject to intense debate. This new interpretation of the politics of the late-fourteenth century offers an in-depth survey of Richard's reign from the perspective of one of the leading nobles who came to oppose him, Thomas Beauchamp, the Appellant Earl of Warwick. This is the first full-length study of one of Richard II's opponents to explore not only why the Earl rebelled against the King, but also why Richard lost his throne. Rather than offering the traditional explanation of a subject grown too mighty, Alison Gundy sets Warwick's rule in the context of the political and constitutional framework of the period. The interplay of local and national events helps to reveal Warwick's motives as a long-serving member of the nobility faced with a king determined to rule in a manner contradictory to contemporary political structures.